2004
DOI: 10.1081/cnv-200032980
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and Gemcitabine, As First-Line Chemotherapy, Combined with Trastuzumab in Patients with Advanced Breast Cancer: A Phase II Study Conducted by the Hellenic Cooperative Oncology Group (HeCOG)

Abstract: TGH is a well-tolerated and effective regimen for the first-line treatment of ABC. Randomized comparison between paclitaxel, trastuzumab, and triplets are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
5
34
1
2
Order By: Relevance
“…Two additional Phase II studies by Gori et al [15] and Fountzilas et al [16] of trastuzumab with weekly paclitaxel, confirmed the results by Seidman et al [10].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Two additional Phase II studies by Gori et al [15] and Fountzilas et al [16] of trastuzumab with weekly paclitaxel, confirmed the results by Seidman et al [10].…”
Section: Discussionsupporting
confidence: 52%
“…In vitro studies suggested an additive activity of trastuzumab when combined with paclitaxel [13,14] and several Phase I-II clinical studies have assessed the antitumoral activity and the tolerability of such a combination [12][13][14][15][16][17]. The combination of weekly paclitaxel with trastuzumab [10,15,16] produces extended cumulative exposure to the drug and ameliorates the toxicities associated with the standard tri-weekly administration [17], with mild, non-cumulative, hematologic toxicity allowing its administration for prolonged periods of time [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients participated in ten trials designed and run consecutively by HeCOG, exploring different first-line treatment options for patients with MBC [8][9][10][11][12][13][14][15][16][17]. Information was collected prospectively according to the corresponding trial protocol and deposited in the central HeCOG office database.…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria were previous chemotherapy for advanced disease, symptomatic brain metastases, history of other malignancy (except curatively resected non-melanoma skin cancer or in situ cervical cancer), myocardial infarction within the last 6 months, or other serious illness that would impair the ability of the patient to receive protocol treatment. In two of the studies with trastuzumab administration (HE1199 and HE1100) [14,16], eligibility criteria required histologically proven HER-2/neu overexpression [[25% positive cells by immunohistochemistry or fluorescent in situ hybridization (FISH)-positive]. The current analysis is performed both including and excluding the two trastuzumab studies.…”
Section: Methodsmentioning
confidence: 99%